Exploring EFL Teacher Educators’ Goals in Teaching English Oral Communication Skill - Abid Abid (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
The study reported in this article sought to explore teacher educators’ (TEs) perceived goals in teaching English oral communication in an English Education Program in Indonesia. Using a case study method, data for the present study were collected from all TEs teaching English speaking and listening subjects. A semi-structured interview protocols were carried out in English and Indonesian languages. All interview transcripts were transcribed verbatim and analysed using a thematic analysis method. The findings indicate that many of the TEs stress production when teaching oral communication. When asking about the purposes of teaching speaking or listening, they rarely mentioned any expectations that their PSTs would be independent and knowledgeable when dealing with oral communication breakdowns.  Yet, this does not necessarily suggest any problems with TEs’ teaching practices and may instead indicate limited opportunities for PSTs to learn how to deal with oral communication breakdowns in the classroom. The findings of this study, thus, shed lights into current understanding of how teacher educators in Indonesia engage in the preparation of school English teachers’ candidates in the domain of oral communication skills.